Relationship Between Pre-operative Blood Glucose Level and Length of Hospital Stay in Patients With Renal Cell Carcinoma Undergoing Laparoscopic Nephrectomy - He, Ting; Zhu, Weidong; Wang, Chunying; Lu, Haowen; Wu, Tiange; Pan, Kehao; Chen, Shuqiu; Xu, Bin; Mao, Weipu; Li, Wei; Chen, Ming (Frontiers in Surgery, 2021)
Purpose The aim of this study was to assess the effect of preoperative blood glucose (POBG) levels on the length of stay (LOS) in patients with renal cell carcinoma (RCC) undergoing laparoscopic nephrectomy. Methods We collected clinical data on 338 patients with RCC who underwent laparoscopic nephrectomy between 2014 and 2019. Univariate and multivariate logistic regression and dose-response analysis curves of restricted cubic spline function were used to investigate the relationship between POBG and LOS. Results According to the level of POBG, we divided the patients into three groups: <4.94 mmol/L group, 4.94 to <7.11 mmol/L group and ≥7.11 mmol/L group. According to the dose-response analysis curves, we found that the adjusted risk of LOS >two weeks and LOS >three weeks gradually increased with increasing POBG. In addition, we found that among all patients, patients with POBG levels ≥7.11 mmol/L had a 115% higher risk of LOS>two weeks than patients with POBG levels <4.94 mmol/L (adjusted odds risk [aOR] 2.15; 95% CI 1.11-4.20; p=0.024) and patients with POBG levels ≥7.11 mmol/L had a 129% higher risk of LOS>three weeks than patients with POBG levels <4.94 mmol/L (aOR 2.29; 95% CI 1.16-4.52; p=0.017). Moreover, similar results were observed in the most subgroups analysis. Conclusion We found that in patients with RCC undergoing laparoscopic nephrectomy, higher POBG levels were significantly associated with prolonged LOS.